A Critical Historical Examination of Tracking as a Method for Maintaining Racial Segregation - Todd McCardle (Educational Considerations, 2020)
Using a Critical Race Theory framework, this manuscript examines the scholarly literature on the intersection of tracking and its historical use as a method for establishing and maintaining racial segregation in American public schools. I begin by exploring accounts of tracking in American public educational institutions as researched by historians of education. Then, I examine contemporary manifestations of tracking in American public schools beginning in the 20th century by sociologists of education. Within the discussion of contemporary tracking, I explore the use of tracking through magnet schools in order to circumvent federal legislation aimed at desegregating American public schools. Overall, the intersection of these bodies of literature argues that the problematic roots of tracking continue to maintain historical racial and ethnic segregation in American public schools.
Keywords: tracking; racism; desegregation; history of education